THE PHYSICAL STATE OF THE CULTURE MEDIUM ON THE BEHAVIOR IN VITRO OF BROMELIACEAE - MENGARDA, Liana Hilda Golin; POVOAS, Luciano; DEBIASI, Clayton; PESCADOR, Rosete (Scientia Agraria, 2009)
The objective of this study was to evaluate the effect of the physical state of the culture medium on the behavior in vitro of the bromeliaceas Neoregelia cruenta, Tillandsia stricta, Vriesea gigantea, V. guttata e V. incurvata. Micropropagated shoots had been cultivated in culture medium MS, with 30 g sucrose, 2,5 mg dm-3 BAP, and 0,5 mg dm-3 ANA, establishing the treatments: T1- half-solid with 7 g agar; T2- static liquid; T3- liquid under-agitation of 90 rpm; and T4- static liquid with bridge of paper filter. After 30 days, the use of static way of liquid culture presented better results in relation of proliferative average rate in all the species (9.4 shoots in N. cruenta, 5.6 in T. stricta, 11.5 in V. gigantea, 9.2 in V. guttata and 3.9 in V. incurvata). In relation the average height of the shoots, was distinguished for N. cruenta the liquid under-agitation (2.83 cm), T. stricta and V. incurvata the semisolid (1.76 cm and 2.02 cm, respectively) and V. gigantea and V. guttata the static liquid (0.61 cm and 1.48 cm, respectively). The use of medium MS static liquid was more suitable for in vitro culture of bromeliads species studied.